Getting Lost in the Cell–Lysosomal Entrapment of Chemotherapeutics - Xingjian Zhai (Cancers, 2020)
Despite extensive research, resistance to chemotherapy still poses a major obstacle in clinical oncology. An exciting strategy to circumvent chemoresistance involves the identification and subsequent disruption of cellular processes that are aberrantly altered in oncogenic states. Upon chemotherapeutic challenges, lysosomes are deemed to be essential mediators that enable cellular adaptation to stress conditions. Therefore, lysosomes potentially hold the key to disarming the fundamental mechanisms of chemoresistance. This review explores modes of action of classical chemotherapeutic agents, adaptive response of the lysosomes to cell stress, and presents physiological and pharmacological insights pertaining to drug compartmentalization, sequestration, and extracellular clearance through the lens of lysosomes.